Pengaruh Ekspektasi Dan Fasilitas Terhadap Kepuasan Wisatawan Di Ragentar Glamping Umbul Sidomukti - Saptiany, Shella Gherina; Octafian, Ray; Putri, Julian Andriani; Susilaningtyas, Gesit; Oktavianto, Ibnu Farhan (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
This research aims to investigate the extent to which expectations and facilities at RaGentar Glamping influence tourist satisfaction. Expectations refer to tourists' hopes or anticipations about the experience they will receive when visiting RaGentar Glamping, while facilities refer to the features and services provided by the accommodation, such as the quality of accommodation, food, recreational facilities, and customer service. The research sample consists of a number of tourists who have visited RaGentar Glamping. Through surveys or interviews, respondents were asked to evaluate their expectations before the visit, as well as assess their satisfaction after experiencing the facilities at RaGentar Glamping.The results of the data analysis indicate that there is a significant relationship between expectations and facilities with the level of tourist satisfaction. This means that the higher the expectations and the quality of facilities provided by RaGentar Glamping, the higher the level of satisfaction experienced by tourists. This underscores the importance of paying attention to and enhancing the quality of services and facilities provided by RaGentar Glamping to improve the experience and satisfaction of visitors.